Indonesia's Presidential Threshold: An Analysis of Legal and Political Dynamics - Mohammad Akbar Maulana Rahman; Reinaldo Francisco Luis; Ahmad Sholikhin Ruslie (CV. Era Digital Nusantara, 2023)
Abstract: The presidential threshold is the nomination requirement employed by political parties to select the President and Vice President. In Indonesia, the regulation governing the presidential threshold is outlined in Article 222 of Law No. 7/2017 on General Elections. This article stipulates that candidate pairs must be proposed by political parties or a coalition of political parties participating in the elections, provided they meet the criteria of obtaining at least 20% of the total seats in the DPR (The House of Representatives of the Republic of Indonesia) or obtaining 25% of the national valid votes in the previous DPR elections Purpose: This study aims to determine the political dynamics of threshold presidential regulation law in Indonesia. Design/Methodology/Approach: The type used in this research is normative legal research, and uses several approaches, namely the statute approach, conceptual approach, and historical approach. Findings: In principle, the regulation of the presidential threshold is an open legal policy or open legal policy of the legislator, but its application in Indonesia, the presidential threshold has shortcomings because first, it makes legislative elections a prerequisite for the presidential election, and second, the legislative elections that are used as requirements have occurred in the previous election period, which in terms of political configuration is certainly different from the elections that will take place or are taking place. The application of the presidential threshold in Indonesia is also inappropriate because 1) it eliminates independent Presidential candidates; 2) it excludes the participation of non-parliamentary political parties to determine their own Presidential candidates; 3) it only benefits established/large political parties; 4) it is not suitable if applied in a presidential system, because the President in this system is not responsible to parliament; 5) the emergence of transaction politics; and 6) the limited number of choices of Presidential candidates offered. Originality/Value: There has not been much research on presidential threshold arrangements in their formation, especially based on the political dynamics of law that developed during the formation process